Organizational Internal Factors and Sustainable Performance: A Serial Mediation Model - Ejaz, Faisal; Abid, Sidra; Nasir, Aemin; Esponda-Pérez, Jorge Alberto; Ejaz, Sarmad; Hossain, Md Billal (Ital Publication, 2025)
Objective: The present study aims to explore the relationships between big data analytics capability, circular economy practices, and SMEs’ sustainable performance in Pakistan. It investigates notable factors determining SMEs’ sustainable performance, including employees’ perceived usefulness, data-driven culture, and leadership competency mediating the mentioned relationships. Method: The study employs quantitative research based on a positivist philosophy orientation. Data were collected through a structured questionnaire distributed among the employees of 350 SMEs operating in Pakistan’s different regions. Findings: The study's results demonstrated the direct effects of big data analytics capability on sustainable performance, employee perceived usefulness, and data-driven culture. Additionally, circular economy practices influence sustainable performance; employee perceived usefulness and leadership competency. Finally, the results highlighted that each relationship is subject to partial mediation, which indicates the role of employee-perceived usefulness and data-driven culture in the relationship between big data analytics and sustainable performance and employee-perceived usefulness associated with the relationship between circular economy practices and sustainable performance. Novelty:The present study highlights that all three of the previous topics are consistent and significantly contribute to the existing literature by providing a model with the main factors that determine SMEs’ sustainable performance, which can be sufficient for countries’ developing economies. Doi: 10.28991/ESJ-2025-09-01-020 Full Text: PDF